Affective and emotional dysregulation as pre-dementia risk markers: exploring the mild behavioral impairment symptoms of depression, anxiety, irritability, and euphoria. (13th September 2017) - Ismail, Zahinoor; Gatchel, Jennifer; Bateman, Daniel R.; Barcelos-Ferreira, Ricardo; Chantillon, Marc; Jaeger, Judith; Donovan, Nancy J.; Mortby, Moyra E.
ABSTRACT: Background: Affective and emotional symptoms such as depression, anxiety, euphoria, and irritability are common neuropsychiatric symptoms (NPS) in pre-dementia and cognitively normal older adults. They comprise a domain of Mild Behavioral Impairment (MBI), which describes their emergence in later life as an at-risk state for cognitive decline and dementia, and as a potential manifestation of prodromal dementia. This selective scoping review explores the epidemiology and neurobiological links between affective and emotional symptoms, and incident cognitive decline, focusing on recent literature in this expanding field of research. Methods: Existing literature in prodromal and dementia states was reviewed, focusing on epidemiology, and neurobiology. Search terms included: "mild cognitive impairment, " "dementia, " "prodromal dementia, " "preclinical dementia, " "Alzheimer's, " "depression, " "dysphoria, " "mania, " "euphoria, " "bipolar disorder, " and "irritability." Results: Affective and emotional dysregulation are common in preclinical and prodromal dementia syndromes, often being harbingers of neurodegenerative change and progressive cognitive decline. Nosological constraints in distinguishing between pre-existing psychiatric symptomatology and later life acquired NPS limit historical data utility, but emerging research emphasizes the importance of addressing time frames between symptom onset and cognitive decline, and age of symptom onset. Conclusion: Affective symptoms are of prognostic utility, but interventions to prevent dementia syndromes are limited. Trials need to assess interventions targeting known dementia pathology, toward novel pathology, as well as using psychiatric medications. Research focusing explicitly on later life onset symptomatology will improve our understanding of the neurobiology of NPS and neurodegeneration, enrich the study sample, and inform observational and clinical trial design for prevention and treatment strategies.